EPCO-19. INTEGRATED ANALYSIS OF INTRA-TUMORAL HETEROGENEITY IN GLIOBLASTOMAS THROUGH SINGLE NUCLEI ATAC-SEQ AND RNA-SEQ. (9th November 2020) - Raviram, Ramya; Raman, Anugraha; Preissl, Sebastian; Ning, Jianfang; Wu, Shaoping; Deynze, Kinsey; Chen, Clark; Ren, Bing
Abstract: Glioblastoma, the most common form of primary brain cancer in adult, consists of an ecosystem of cancer cells characterized by cell-to-cell variations in genotypes and phenotypes. This intra-tumoral heterogeneity forms the substrate for cancer evolution, which in turn fuels therapeutic failure and resistance. To better define this heterogeneity, we profiled clinical glioblastoma specimens using single nuclei assays for Transposase-Accessible Chromatin with sequencing (snATAC-seq), RNA-Seq (snRNA-Seq), Paired snATAC/snRNA-seq, and whole genome-seq (WGS). We found that snATAC-Seq detected focal amplifications ( 40kb-2MB) of genomic regions, revealing magnitudes of intra-tumoral heterogeneity previously unappreciated. snATAC-seq and WGS provided high resolution chromatin-state maps of extrachromosomal DNA (ecDNA), while Paired-seq delineated gene expression patterns associated with these chromatin-states. sn-RNAseq confirmed distinct cell states previously defined by others, including oligodendrocyte progenitor cell (OPC), neural progenitor cell (NPC), astrocyte, and mesenchymal -like glioblastomas. Analysis of snATAC-seq profiles in this context revealed shared dependency of these cell states on the Nuclear Factor 1 complex (NFIA and NFIB). Our results demonstrate the utility of cross-platform integration of single cell genomic technologies and suggest that, despite the overwhelming genotypic and phenotypic heterogeneity, shared vulnerability of predominant glioblastoma cell states can be identified.